Maqashid Syari'ah Index Model in Sharia Bank - Ridwan, Mukminati; Pagalung, Gagaring; Luthfi, Mukhtar; Amin, Abd Rauf Muhammad (Bukhori: Kajian Ekonomi dan Keuangan Islam, 2023)
Purpose: This study aims to identify the appropriate model for measuring the level of Maq'hid syar'ah in sharia banking. Methodology: The method used is a qualitative method with a literature approach. The data used are the results of published research using the Maq'hid syar'ah index with the study object of sharia banking. Results: The results of the study indicate that there are 5 measurement concepts used in measuring the sharia-compliancy of Sharia banks using the Maq'hid syar'ah index. Of the five concepts, there is a fundamental similarity that is the key to achieving the goal of Maq'hid syar'ah, which is purifying the soul, justice, and public welfare. A simple model that can be used to measure quantitatively is by using 3 main instruments; Interest-free business for the purpose of purifying the soul, Zakat for the purpose of achieving justice, and real investment for the purpose of realizing welfare (maslaha).